Jongo na escola: contribuições para e na educação das relações étnico-raciais - Silva, Vívian Parreira da (2020)
We believe that doing science and building knowledge is also a way of fighting oppression, assimilation, epistemicide, interdiction and against the impediments suffered by men and women for wanting to exist with their diversities.The jongo is the centrality of this work. We will enter the circle to propose as a thesis the jongueira education that displaces epistemic centralities fixed in the colonial bases of racism. Therefore, it is a humanizing, liberating education, that recreates existences and possibilities. The jongo is the impulse that invites us to live education as an enchantment and challenge together with the children and the teacher who collaborated with this research. This study aimed to understand how the educational processes resulting from a jongo intervention, carried out in a school in the city of São Carlos with children aged six and seven in the second year class, contribute to making the implementation of law 10.639/03 (Brasil, 2003). It is a qualitative research, as a methodological path we chose the systematization of experiences, which allows the exchange and sharing of knowledge from the critical interpretation of the intervention or educational practice. Each step of this methodological procedure consists of elements that help us to conduct the systematization process. Data collection was carried out between the months of August and December 2018 and was recorded in field diaries, audios and videos. In the data analysis, the following thematic categories emerged: Knowing, receiving and sharing: knowledge lived as an anti-racist struggle; Corporeality and Belonging: the body as a port, space and time for learning; Affection and School: researching with children and building knowledge in living together; Time to learn and teach. The educational processes experienced with the children and the teacher were based on sharing, affection, collaboration, and the recognition of the potential of jongo as an anti-racist pedagogy. In this way, these educational processes, in the experience of the jongo, proved to be powerful methodological paths for the implementation of Law 10.639 / 03. We affirm the jongueira education as an education that promotes life, presence and enchantment, which, versed in the crossing of knowledge and in dialogue with the school, gives us the basis for exercising different explanatory principles of the world based on the pluriversality of knowledge.